Aumento de la población, presión sobre el ecosistema y seguridad alimentaria: el caso de las comunidades pesqueras del golfo de Urabá (2018)
ABSTRACT:There is a relationship between the increase of a population and the pressure it exerts on the ecosystem. In this sense, this article reflects on the fishing communities that inhabit the Gulf of Urabá and its food security situation. Reflection: The Gulf of Urabá, with its mangrove littoral, has fed the populations that have long lived on its shore; however the situation of forced displacement experienced in the region has increased the number of inhabitants of the fishing communities. Fishing has become the source of food and sustenance for old and new settlers, which has led to over-exploitation of marine resources, deterioration of the ecosystem, reduced availability of food, and has led to food insecurity of the inhabitants of the gulf shore. Conclusions: The food security situation of the fishing communities needs to be understood in its context, its ecosystem, and daily life; it also requires transdisciplinary work, beyond nutrition, and requires attention to design and implementation of concerted alternatives for and with the villagers.